2006
DOI: 10.1007/s10147-006-0610-5
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation study of docetaxel and nedaplatin in patients with relapsed or refractory squamous cell carcinoma of the esophagus pretreated using cisplatin, 5-fluorouracil, and radiation

Abstract: The recommended doses of docetaxel and nedaplatin were 30 and 80 mg/m(2), respectively. This combination could be a potential second-line treatment for this target population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…Clinically, an association has been observed between NDP and an improved response in DDP-resistant cancer (13,30,31). Therefore, in the present study, the effect of NDP on A549DDP cells was analyzed by in vitro experimentation, which has not yet been verified in any previous findings.…”
mentioning
confidence: 73%
“…Clinically, an association has been observed between NDP and an improved response in DDP-resistant cancer (13,30,31). Therefore, in the present study, the effect of NDP on A549DDP cells was analyzed by in vitro experimentation, which has not yet been verified in any previous findings.…”
mentioning
confidence: 73%
“…The reasons why we adopted this protocol were as follows: (1) Yoshioka et al [23] reported the optimum dosing of docetaxel and nedaplatin was 30 mg/m 2 and 80 mg/m 2 , respectively, in the phase I study.…”
Section: Treatment Schedulementioning
confidence: 99%
“…In a phase II clinical study of single-agent nedaplatin for esophageal cancer, the overall response rate was 51.7% (15/29) [22]. Yoshioka et al [23] evaluated the feasibility of combination chemotherapy using docetaxel and nedaplatin for recurrent ESCC, and achieved complete and partial responses in 3.6 and 35.7% of patients, respectively. Combination chemotherapy using docetaxel and nedaplatin was recently suggested as a treatment for recurrent ESCC in outpatient settings [24].…”
Section: Introductionmentioning
confidence: 99%
“…Nedaplatin exerts anti-tumor effects following uptake into tumor cells by binding to DNA bases and inhibiting DNA replication, similar to cisplatin and carboplatin (5). However, the ability of cancer cells to become resistant to nedaplatin remains a notable obstacle to successful chemotherapy; resistance of numerous species of cancer cells to nedaplatin can be reversed by combining with chemotherapeutic agents, including 5-fluorouracil, docetaxel and vindesine (6)(7)(8). The identification of new chemotherapy regimens incorporating nedaplatin with other chemotherapeutic agents can enhance the knowledge of nedaplatin resistance and support the development of nedaplatin-based approaches to cancer therapy.…”
Section: Introductionmentioning
confidence: 99%